Etyka w działalności samorządu terytorialnego - Stawecki, Marek (Annales. Etyka w Życiu Gospodarczym, 2009)
Corruption is an actual threat to democracy as it impairs the citizens’ trust towards the state. Therefore, it is necessary to undertake any actions that would prevent it; actions that would promote the formation of ethical structure in all departments of administration, as well as would build an ethical awareness among local government employees and city councilors. Ethical behaviour is dependent on clear procedures, good regulations and their proper interpretation. The principal objective should be to increase the citizens’ trust towards public administration and to improve administrative work. That is why one of the most obvious techniques (but not the only one) of raising ethical standards is to implement an adequate system of choice and selection of employees. In Poland, when the moral standard of a candidate for a post in public administration comes under close scrutiny, any doubts are quite often eliminated by the assumption that, if the candidate is patronized by a third party, its authority is a warrant of his or her adequate ethical standard. Of course, it’s a wrong point of view. The above-mentioned examples indicate that the rules of ethics should be introduced to public administration work because they guarantee that the quality of services will be good, they will neutralize corruption and, if followed, they will enable preparing public administration officers and local government representatives to assume responsibility for their actions.